Nudging Parents to Increase Preschool Attendance in Uruguay - Nicolas Ajzenman; Laura Becerra Luna; Juan Manuel Hernández-Agramonte; Florencia López Bóo; Marcelo Perez Alfaro; Alejandro Vásquez-Echeverría; Mercedes Mateo Díaz (Institute of Labor Economics (IZA), 2021)
This paper presents the results of a nationwide very low-cost behavioral intervention aimed at increasing preschool attendance in Uruguay. Specifically, behaviorally-informed messages were delivered through the government's official mobile app. We document a large reduction in absenteeism, as well as an increase in some measures of cognitive development, though only for children around the median of the attendance rate baseline distribution (between deciles 4 and 6). The intervention was ineffective for children with very high or very low pre-treatment absenteeism levels. Our results, although encouraging, emphasize the limits of these types of interventions, especially for children in families where barriers to reduce absenteeism might be structural rather than behavioral.
Keywords: D9; I2; 330; preschool attendance; behavioral; cognitive development